Indigo Naturalis (青黛) Comes from Blue, but it Excels Blue - Tianwen Yao; Baican Yang (Wolters Kluwer Health/LWW, 2019)
Indigo naturalis (青黛) is also called "indigo flower," "bright cyan," and "cyan clam powder." The alias "indigo flower" shows its complex progress about producing dyes. The alias "bright cyan" vividly displays the visual characteristics of indigo naturalis. Its another alias "cyan clam powder" implies its properties, flavors, and particular morphologic characteristics. The name of "indigo naturalis" emphasizes its wide use in ancient times to paint their eyebrows. Indigo naturalis, which comes from the Persian Kingdom, wins the favor and praise of customers in the respects of dye and cosmetics in both Eastern and Western Regions. It not only shows the infinite charm of dye culture in the Western Regions and provides a visual sensation for people, but also adds new color for Chinese medicine culture.